Determinants of Tourism and HIV/AIDS Incidence in West Java - Heriana, Cecep; Suparman, Rossi; Rana, Sohel; Sukmanawati, Dera (UI Scholars Hub, 2018)
Indonesia defined as tourist destination where the international and domestic tourists enjoy the tourist attractions. Prostitution existing in tourism place may increase the prevalence of HIV/AIDS. The incidence and spread of AIDS in many areas in West Java is a problem for tourism industry. These issues become acute in locations where sexual attraction is used as a determinant of tourist portability. The aim of this study was to determine relation between tourism and the incidence of HIV/AIDS in West Java. Non-reactive research design was used to collect secondary data from the Central Bureau of Statistics in 2016 from 26 districts/cities in West Java. This study was conducted in January - October 2016. Univariate and bivariate analysis methods with Spearman’s statistical test and multivariate analysis (multiple logistic) were applied. Bivariate analysis results showed the number of star hotels had p value = 0.003, r = -0.552), visit to accommodation had p value = 0.009, r = 0.499) and average guest per day had p value = 0.022, r = 0.447. Results of multivariate analysis showed that accommodation visits had p value = 0.000). In conclusion, tourism determinants associated with the incidence of HIV/AIDS are the number of star hotels, visits to hotel, and the average guest per day.